Unmaking Manly Smokes: Church, State, Governance, and the First Anti-Smoking Campaigns in Montreal, 1892-1914 - Rudy, Jarrett (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2001)
AbstractThis paper examines a series of anti-smoking campaigns by the Montreal Women's Christian Temperance Union that were part of local, provincial, and federal campaigns for age restrictions on smoking and cigarette prohibition. The Montreal campaigns were particularly unsuccessful in comparison to those undertaken in other provinces. The article argues that while women's exclusion from formal politics and the particularly masculine symbolism of smoking were important factors in accounting for the weakness of the Montreal WCTU's campaigns, the specificity of the Montreal case is found in the religious demography of the city. The paper uncovers the social gospel beliefs of the Montreal WCTU and the theological roots of anti-prohibitionists in the city. Ultimately, the question is situated in a debate over the liberal order at the turn of the twentieth century and the proper role of the church and state in the moral formation of individuals.